Causes of variation in littoral fish communities of the Eastern Baltic Sea: from community structure to individual life histories - Taal, Imre (2017)
Väitekirja elektrooniline versioon ei sisalda publikatsioone Litoraalialad on vee-elustikule oluliseks sigimis-, kasvu- ja toitumisalaks. Muutlike abiootiliste ja biootiliste keskkonnategurite koosmõjul varieerub litoraalialade kalakoosluste liigiline koosseis väga suurel määral nii ajas kui ka ruumis. Käesoleva töö eesmärkideks oli välja selgitada: 1) Läänemere litoraali asustavate kalaliikide ööpäevaringseid ja aastasiseseid käitumismustreid; 2) litoraali kalastiku sesoonse toitumisökoloogia eripärad meritindi näitel; 3) anadroomsete kalade (lõhe ja meriforell) noorjärkude alternatiivseid rändestrateegiaid jõgede ja Läänemere litoraalialade vahel. Selgus, et: 1) Läänemere litoraali asustavate kalaliikide ööpäevaringne käitumine on seni kirjeldatust oluliselt mitmetahulisem. Seega, mingi konkreetse litoraali piirkonna ööpäevas muutuva liigilise koosseisu täielikuks kirjeldamiseks on vajalik proovipüükide tegemine nii hommikul, keskpäeval, õhtul kui ka öösel; 2) Läänemere idaosa litoraaliala asustava meritindi toitumiskäitumine erineb avamere elupaikades kirjeldatust; 3) Läänemere riimveelised litoraalialad võivad olla seni arvatust olulisemaks kasvualaks alternatiivseid rändestrateegiaid kasutavatele lõhilaste noorjärkudele; 4) läbi riimvee vooluveekogu vahetavad noorkalad võivad osaliselt olla ka anadroomsete lõhilaste populatsioonides esinevate „eksijate“ varem kirjeldamata tekkemehhanismiks; 5) Läänemere litoraali asustavatel kalaliikidel võib esineda nii piirkonnaspetsiifilisi ööpäevaringseid toitumisrändeid (meritint) kui ka elukäigumustreid (lõhe, meriforell). The shallow littoral is an important reproduction, nursery, and foraging area to coastal marine biota. Due to variability in abiotic and biotic environmental parameters, near-shore fish communities of the Baltic Sea are highly variable. Thus, the occurrence and abundance of fish species may be spatially and temporally highly variable. The objectives of the present thesis were to: 1) assess diel variations in the composition of the fish assemblage in the surf-zone of the non-tidal Baltic Sea; 2) estimate the predatory role of European smelt in a littoral habitat by describing seasonal variation of prey composition; 3) investigate whether littoral zone of the Baltic Sea also function as a habitat for early out-migrating Atlantic salmon and anadromous brown trout (ABT) fry and parr. The main results and conclusions are the following: 1) fine-scale variations in littoral fish assemblages are more complex and may take place within shorter time frame than previously known; 2) European smelt inhabiting littoral areas of the Baltic Sea occupy different ecological niche than smelt in offshore areas; 3) alternative migrations of juvenile salmonids between freshwater and brackish environments indicate that the shallow littoral zone of the Baltic Sea may play a significant role as a permanent or provisional nursery area to these species; 4) the phenomenon of stream shifting through the marine environment may constitute at least one possible mechanism behind the straying behaviour documented during the spawning runs of Atlantic salmon and ABT in the Baltic Sea basin; 5) some coastal fish species inhabiting the Baltic Sea might show sub-basin specific behaviour in terms of their regular diel movements and alternative life history patterns